POTENSI PENGGUNAAN ANGKUTAN INFORMAL DI KOTA BANDUNG - Bahar, Taslim; Kusbiantoro, B.S.; Z. Tamin, Ofyar; Bona Frazila, Russ (Jurnal Transportasi, 2011)
Limited size of the road dimension in an area could prevent formal public transport (four-wheeled vehicles) to serve the area. This condition led to the rise of public transport alternatives, such as motorcycle ojek, with flexible routes and rates. Currently, their operation and service tend to increase in many cities in Indonesia. This study aims to determine the potential use of ojek as an alternative to public transport in urban areas.Analyses were performed using the causal relationship between services quality factors with the satisfaction and loyalty of users, using the Structural Equation Modeling (SEM) method. The results showed that more than 70% of users who will continue to use motorcycle ojek for a long time, especially in suburban areas, and about 30% are likely to switch to alternative modes, especially users with the end destination of employment.Keywords: motorcycle-ojek, user satisfaction, user loyalty.